Розв'яжіть з 7. по 13.

Розв'яжіть з 7. по 13.
Гость
Ответ(ы) на вопрос:
Гость
7) x³-3x²-4x +12=0 x²(x-3)  + 4(-x+3)=0 x²(x-3) - 4(x-3)=0 (x-3)(x²-4)=0 (x-3)(x-2)(x+2)=0 произведение =0 , если один из множителей =0 х-3=0 х₁=3 х-2=0 х₂=2 х+2=0 х₃=-2 8) х³ -4х²-4х+16 =0 х²(х-4) -4(х-4)=0 (х-4)(х²-4)=0 (х-4)(х-2)(х+2) =0 х-4=0 х₁=4 х-2=0 х₂=2 х+2=0 х=-2 9) (х²-25)/(х-5) =0 знаменатель ≠0 х-5≠0 ;   х≠5 ((х-5)(х+5) ) / (х-5)=0         (дробь сокращается) х+5 =0 х=-5 10) (х²-9) /(х+3)=0 х+3≠0 ;  х≠-3 (х²-3²)/ (х-3)=0 ((х-3)(х+3)) /(х+3)=0 х-3=0 х=3 11) [(х+2)/(х²-2х) ] -   [ x/(x-2)] = 3/x          x²-2x≠0   ;  x(x-2)≠0  ;   x≠0    ;  x≠2 [ (x+2) / x(x-2)]   - [ x/(x-2)]  = 3/x       | *x (x-2) x+2    -  x*x = 3(x-2) -x² +x+2 = 3x-6 -x² +x+2-3x+6 =0 -x² -2x+8 =0              |*(-1) x²+2x-8 =0 D = 2² -4*1*(-8) = 4+32=36=6² x₁= (-2+6)/ (2*1) = 4/2 =2    -не подходит , т.к. знаменатель ≠0 х₂= (-2-6)/2 = -8/2 =  -4 Ответ: х=-4 12) [(4x-4)/x ]   + [ (x²+4)/ (x²+x) ]  = [ (6+x)/ (x+1) ]      | * x(x+1) x²+x ≠0 ;    x(x+1)≠0  ;  х≠0 ;   х+1≠0 ;  х≠-1 (4x-4)(x+1)  + x²+4 = x(6+x) 4x²+4x -4x-4  +x²+4 = 6x+x² 5x² -6x-x²=0 4x²-6x=0 2x( 2x -3 ) =0 2x=0 x=0  - не подходит 2х-3 =0 2х=3 х=3/2 х=1,5 13)  [x/(x+2) ]   + [ (x+2)/(x-2) ] =  [ 8 / (x²-4) ]    [x/(x+2)] + [(x+2)/(x-2) ] = [ 8/ (x-2)(x+2) ]              | * (x-2)(x+2) x+2 ≠0   ;   х≠ -2 х- 2 ≠0  ;    х≠ 2  x(x-2) +(x+2)(x+2) = 8 x²-2x + (x+2)² =8 x²-2x +x² +2*2x +2² =8 2x² +2x +4-8 =0 2x²+2x-4 =0             |÷2 x²+x-2=0 D= 1² -4*1*(-2) = 1+8=9 =3² x₁= (-1-3)/ (2*1) = -4/2 =-2    не подходит х₂= (-1+3)/2 = 2/2 = 1 Ответ: х=1
Не нашли ответ?
Ответить на вопрос
Похожие вопросы